2016
DOI: 10.1021/acs.energyfuels.6b01776
|View full text |Cite
|
Sign up to set email alerts
|

Methane and Carbon Dioxide Adsorption on Illite

Abstract: The adsorption of CH4 and CO2 onto illitic clay was investigated at the temperatures 298, 313, 328, 358, and 423 K (25, 40, 55, 85, and 150 °C) over a range of pressures up to 50 MPa using grand canonical Monte Carlo (GCMC) simulations. Our simulation results showed spontaneous and exothermic adsorption behavior of illite for CH4 and CO2 with enthalpy changes of −3.50 kJ/mol and −25.09 kJ/mol, respectively. Our results indicated that the interlayer counter cations (K+) play an important role in CO2 adsorption.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 46 publications
10
92
0
Order By: Relevance
“…This conclusion is in accord with the results of the isothermal adsorption experiments performed by Ji et al who found that high temperatures impeded methane adsorption by illite. This observation was also reported by Mosher et al, Zhang et al, and Xiong et al, who found that the methane adsorption capacities of carbon and minerals decreased with increasing temperature. Furthermore, Figure A shows that the range of maximum pressure was between 16 MPa and 18 MPa when the temperatures were between 313 K and 373 K, which is in disagreement with previous reports .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This conclusion is in accord with the results of the isothermal adsorption experiments performed by Ji et al who found that high temperatures impeded methane adsorption by illite. This observation was also reported by Mosher et al, Zhang et al, and Xiong et al, who found that the methane adsorption capacities of carbon and minerals decreased with increasing temperature. Furthermore, Figure A shows that the range of maximum pressure was between 16 MPa and 18 MPa when the temperatures were between 313 K and 373 K, which is in disagreement with previous reports .…”
Section: Resultssupporting
confidence: 88%
“…These studies indicated that the GCMC method has been proven to be an effective method for investigating of the microcosmic adsorption mechanisms of adsorbents and have obtained some knowledge regarding methane adsorption by clay minerals. In addition, Zhang et al and Chen et al studied the adsorption behaviors of CH 4 , CO 2 , and their mixtures of illite using the GCMC and MD methods. In these studies, the total gas amounts and excess adsorption amounts of clay minerals were used to investigate the methane adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…This is a typical characteristic of the excess adsorption of supercritical fluids on solids [28]. The maximum excess adsorption occurs at a certain pressure where the rate of densities of the adsorbed and free phases is changing at the same rate with pressure [26,28]. Moreover, significant hysteresis can be seen between the adsorption and desorption isotherms for each sample.…”
Section: Contains a List Of The Key Reservoir And Wellmentioning
confidence: 95%
“…A constant adsorbed phase density (ρ ads ), obtained as the value of the bulk gas density (ρ bulk ) at which the measured excess adsorption isotherm is zero [26], was applied for the conversion of excess sorption isotherms to absolute isotherms. At zero excess adsorption, the adsorbed gas is identical to and indistinguishable from the free bulk gas, and as such, the adsorbed phase density at saturation can be taken as the density of the bulk gas at this point [26].…”
Section: Measurements and Modeling Of Methane Adsorption And Desorptimentioning
confidence: 99%
See 1 more Smart Citation